Merunut Potensi Kopi Arabika Sebagai Pengusung Utama Komoditas Ekspor Provinsi Bali - Sarjana, I Dewa Gede Raka; Darmawan, Dwi Putra; Astiti, Ni Wayan Sri (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2017)
ABSTRACT Treating Arabica Coffee Potentials as a Main Sector of The Export Commodity Bali Province The last 5 years of Balinese economic growth has been stagnant (on average 5.5%), while it is better than the national economic growth (5.02%). Given these facts, Balinese economic development needs to be directed to the source of new economic growth to create a progressive, inclusive and equitable acceleration of economic growth towards the equity of the wider society. In line with this intention, this study aims to map the potential industry which then becomes the candidate for new economic growth. This study was using a descriptive research design, in which the researchers interacted intensely with key informants and various sources of reference, related to the field under study. Methodologically these assessment activities may include careful study (observation, fieldsurvey and documentary studies of the potential of arabica coffee that can be identified as future business opportunities. Coffee plants (Coffee Sp.) in addition to having a strategic value in the economic development of society, especially in rural areas. Its role is increasingly important considering the coffee garden place the highest position in terms of coffee ownership in the province of Bali. The development of the last 10 years, increased the area of planting area by 3.04%, production by 27% per year, and the productivity (ose) an average of 1000 kg/ha/year. Until now Bali province ranks the top 10 coffee producers in Indonesia with planting area of 23,614 ha for Robusta and 9,448 ha for Arabica. The contribution of Arabica coffee to Bali’s coffee export commodity recently shows a significant increase in both quantity and quality. In terms of overall potential in Bali (22,974 ha), most (20,840 ha) are located in 4 arabica coffee producer regencies, including: Bangli (12,589 ha); Karangasem (3,419 ha); Buleleng (3,400 ha) and Badung 1,413 ha. However, in its development until 2014 the potential area can only be realized as a community plantation of 9,780 ha covering 3 regencies such as: Bangli, Buleleng and Badung, so there is still a potential remaining 46.4% of Bali's potential as a whole. In terms of production quality, the three production centers have excellent taste quality (the test results are rated Very Good-Excelent by the score 7-8), so it is now known as Balinese coffee and classified having Geographical Indication with lemon flavor. Keywords: Economic growth; the potential of Arabica coffee, and; Balinese coffee